2014
DOI: 10.2514/1.c031434
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamics of Deformable Thin Airfoils

Abstract: Unsteady aerodynamic theories are essential in the analysis of bird and insect flight.The study of these types of locomotion is vital in the development of flapping wing aircraft. This paper uses potential flow aerodynamics to extend the unsteady aerodynamic theory of Theodorsen and Garrick (which is restricted to rigid airfoil motion) to deformable thin airfoils.Frequency-domain lift, pitching moment and thrust expressions are derived for an airfoil undergoing harmonic oscillations and deformation in the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This method can also be applied to morphing airfoils [124]. In addition, there are some other aerodynamic theories that take into account the flexibility of the wing [125,126]. For example, Johnson et al [125] summarized the systematic application of von Kármán and Sears' extended unsteady thin airfoil theory to general morphing airfoils.…”
Section: Unsteady Flow Field Solution Technologymentioning
confidence: 99%
“…This method can also be applied to morphing airfoils [124]. In addition, there are some other aerodynamic theories that take into account the flexibility of the wing [125,126]. For example, Johnson et al [125] summarized the systematic application of von Kármán and Sears' extended unsteady thin airfoil theory to general morphing airfoils.…”
Section: Unsteady Flow Field Solution Technologymentioning
confidence: 99%
“…For distributed flexibility with a low mass ratio, Floryan and Rowley used the Chebyshev numerical method to elucidate the propulsive performance and the optimal distribution of flexibility of the passively flexible foil and revealed that thrust increment will accompany power consumption when the stiffness is large (Floryan & Rowley 2020). While the Chebyshev series method seems the standard method to determine the deformation of the foil and the fluid flow through the collocation procedure (Walker & Patil 2014;Moore 2017), it has obviously simplified the direct two-dimensional fluid solver, which makes rapid searching of all possible material distributions possible. However, the numerical solution from the Chebyshev series method makes the correlation between the performance of the foil and the physical parameters still less clear, which calls for the development of closed-form theory to this flow-structure interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an S-shaped aircraft airfoil, Reid and Kozak (2006) studied the change of the maximum lift-to-drag ratio and the separation bubble position of the airfoil at different Reynolds numbers by changing the airfoil shape design parameters. Based on the potential flow theory, Walker and Patil (2014) created a kind of harmonic deformation thin airfoil similar to the S-shaped inverted arch airfoil. By changing the parameters in the theoretical model, the aerodynamic and aeroelastic characteristics of the harmonic thin airfoil were optimized.…”
Section: Introductionmentioning
confidence: 99%